Comparative anatomical study of anatomical parameters of Pinus sylvestris leaf of different geographical origin - Тулешова, К.; Қали, А.К. (Fundamental and Experimental Biology, 2023)
Bioindication based on the state of morphological and anatomical indicators of plant leaves is a convenient way to assess the state of the environment. Central Kazakhstan, which includes the Karaganda and Ulytau regions, is a region with significant industrial emissions. The purpose of this study is to conduct a comparative study of anatomical indicators of Pinus sylvestris leaves growing in settlements of Central Kazakhstan. The results showed that the maximum parameters of leaf length and width, mesophyll thickness were found for Satpayev city, leaf epidermal thickness for Zhezkazgan city, reservoir diameter for Balkhash city, conducting beam length for Karaganda city, and conducting beam width for Balkhash city. Most of the signs varied at a low and medium level, a high coefficient of variation was noted only for the diameter of the containers (resin passages) of pine needles. It was noted that the minimum indicators of the anatomical structures of Pinus sylvestris needles were found for industrial settlements of Central Kazakhstan: Karaganda, Balkhash, Temirtau and Zhezkazgan, while for Ulytau settlement and Satpayev town all values were at an average and high level. The obtained data can be used for bioindication using green spaces.